The history of archives in Central Asia: ancient times - Sherzodjon Choriyev; Guljahon Shaydullaeva; Zumrad Raxmonkulova (Історія науки і техніки, 2023)
The article devoted studies of the documents on the history of the archives in Central Asia on the basis of archeological researches having been conducted in Central Asia over the last decades. Until now there have not been conducted practical complex studies of Central Asian archives of ancient times. On the basis of certain facts this following article has described the life experiences of ancient people who lived in the territory of current Uzbekistan and indicated the process of preserving documents and transferring data from generation to generation in the form of rock paintings and archival documents-libraries. These references indicate to the existence of ancient scripts in Khorezm. On the basis of scientific studies of the scientists it can be concluded that the elements of scripts discovered on the ancient ceramic handcrafts may be considered as the samples of early economic archieves found in the territory of present Uzbekistan. In the period of Akhamanids in Iran and in Central Asia cuneiform was widespread and in the whole territory of the empire Aramaic script wasn’t the only language of paperwork. As it has been indicated in the article, according to its geographic scope, the Bactrian language took the second place after the Sogd language which was widely used in the territory extending from India to Eastern Turkestan. The fact that two biggest empires as Kushanids and Ephtalits and then also the state of Takhirids utilised this script demonstrates the significance of the ancient Bactrian language in the lives of ancient nations.  This paper also shows the similar attributes of the Bactrian language used in making negotiations of Surkh-Kutal, Rabotak with the scripts used in the samples of the letters in the documents from the library of Ashurbanipal and with the Het script in which the texts of the anthems, national communal decisions and religious messages were inscribed on the rocks. There are also some evidences proving the existence of particular archives in the residences of ancient rulers of Central Asia in such places as Toprak Kala (Khorezm), and in the mount of Mug’ (Devashtich archives). Particularly in royal archives there was a systematic archival work and such materials as leather and wood were widely used to fix the data. Such documents as personal letters, diplomatic correspondence, contracts and economical records were kept in this period. It also should be noted that paperwork was far more enhanced in this epoch.